HEAVY RAINFALL IN THE R.N. MACEDONIA - Gjeshovska, Violeta; Taseski, Goce; Ilioski, Bojan (University Ss. Cyril and Methodius in Skopje, 2021)
Information on maximum precipitation of a short duration, i.e., knowledge of intensity-duration-probability (i-T-p) curves is highly important for various studies in the field of surface water hydrology, generally in hydrotechnics, water management, traffic, etc. However, such crucial data are often unavailable in different parts of the world due to lack of sufficient measuring stations and also due to unprocessed, raw data. In R.N. Macedonia, data on heavy rainfall that took place in the period from 1956 to 1988 are still in use in practice. The need for updating these data is more than necessary, given that rainfall is an extremely stochastic phenomenon. Annual maximum precipitation registered on pluviographic strips in the period from 1989 to 2020 at eight measuring stations has been analyzed in this paper. Maximum precipitation series with a duration of 5, 10, 20, 40, 60, 90, 150, 300,720 and 1440 minutes have been established for the entire period from 1956 to 2020. All these arrays of data have been tested for homogeneity and statistically processed. The probability of occurrence of maximum annual precipitation has been defined according to the adopted mathematical probability function and the i-T-p curves have been constructed. The results of the analysis are presented in a tabular and graphical form.
Keywords: maximum precipitation, intensity, time duration, probability of occurrence